Vulnerability to Drought and Food Price Shocks : Evidence from Ethiopia - Vargas Hill, Ruth; Porter, Catherine (World Bank, Washington, DC, 2017)
Although the measurement and determinants of poverty have been widely studied, vulnerability, or the threat of future poverty, has been more difficult to investigate due to data paucity. This paper combines nationally representative household data with objective drought and price information to quantify the causes of vulnerability to poverty in Ethiopia. Previous estimates have relied on self-reported shocks and variation in outcomes within a survey, which is inadequate for shocks such as weather and prices that vary more across time than space. Historical distributions of climate and price shocks in each district were used to simulate the probable distribution of future consumption for individual households; these were then used to quantify vulnerability to poverty. The analysis shows that many Ethiopians are unable to protect their consumption against lack of rainfall and sudden increases in food prices. A moderate drought causes a 9 percent reduction in consumption for many rural households, and high inflation causes a 14 percent reduction in the consumption of uneducated households in urban areas. Vulnerability of rural households is considerably higher than that of urban households, despite realized poverty rates being fairly similar. This finding reflects that the household survey in 2011 was conducted during a year of good rainfall but rapid food price inflation. The results highlight the need for caution in using a snapshot of poverty to target programs, as underlying rates of vulnerability can be quite different from the poverty rate captured at one point in time. The results also suggest that significant welfare gains can be made from risk management in both rural and urban areas.